Incidence and Risk Factors for Retinopathy of Prematurity in Premature, Extremely Low Birth Weight and Extremely Low Gestational Age Infants - Yucel, Ozlem Eski; Eraydin, Bilge; Niyaz, Leyla; Terzi, Ozlem (BMC, 2022)
Background The aim of the study was to determine the incidence and risk factors of retinopathy of prematurity (ROP) in premature, extremely low birth weight (BW, ELBW) and extremely low gestational age (GA, ELGA) infants. Methods The medical records of preterm infants who were screened for ROP between January 2012 and December 2020 were retrospectively reviewed. Only one eye of each infant with higher grade ROP was included in the study. BW; GA; medical characteristics; the presence, severity, and need for treatment of ROP were recorded. Infants were divided into groups according to BW (<= 1000 g, 1001-1750 g, > 1750 g) and GA (<= 25w, 26-28w, 29-31w, 32-34w, >= 35w) and data were analyzed. Results Data of 2186 infants were evaluated. The overall incidences of any stage ROP and ROP requiring treatment were 43.5 and 8.0%, respectively. These rates were 81.1 and 23.9% in ELBW (<= 1000 g) infants and were 92.9 and 64.3% in ELGA (<= 25w) infants, respectively. The rates of ROP, the median duration of oxygen therapy and systemic diseases increased significantly as BW and GA decreased. The median duration of oxygen therapy and the rates of sepsis, pulmonary dysplasia (BPD), and intraventricular hemorrhage (IVH) were statistically higher in infants with ROP compared to those without ROP (p < 0.001). Multivariate regression analysis demonstrated that low BW and GA; prolonged duration of oxygen therapy; presence of PDA and necrotizing enterocolitis (NEC) were important risk factors for ROP. Conclusions ELBW and ELGA infants develop higher rates of ROP and severe ROP. Prolonged duration of oxygen therapy, the presence of concomitant neonatal sepsis, BPD, IVH, PDA, and NEC further increases the risk of ROP.
Niyaz, Leyla/0000-0003-2501-1518; Terzi, Özlem/0000-0002-9524-5582; Eski Yucel, Ozlem/0000-0003-4014-6234; Eraydin, Bilge/0000-0003-0036-056X
Keywords: Extremely Low Gestational Age Infants; Extremely Low Birth Weight Infants; Premature; Retinopathy of Prematurity; ROP